A promise of working through - Saville Young, Lisa (PINS-Psychology in Society, 2024)
Hook, Derek (2013) (Post)apartheid conditions: Psychoanalysis and social formation. Basingstoke & New York: Palgrave Macmillan (Series: Studies in the Psychosocial). ISBN 978-1-137-03299-7 hbk. Pages x + 242. (Published in 2014 by HSRC Press. ISBN 978-07969-2458-2 pbk. Pages 252. I approached Hook’s book with some trepidation – waiting for an appropriate build-up of energy with which to tackle his work – being familiar with his writing and with the extent to which it has required multiple readings on my part, while never to disappoint in its depth. However, Hook’s exploration of (post)apartheid conditions surprised me in its accessibility, while not compromising on the depth and complexity of his arguments. The introduction and conclusion provide a comprehensive guide for the reader and throughout the book, Hook draws on recognisable anecdotes, his own experiences and frequent summaries, that enable the reader to remain fully attentive to his more challenging articulations.